(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This scientific article delves into the pressing challenges faced by global geo-financial policy and their influence on international financial relations. The authors conduct an analysis of geopolitical tensions, trade conflicts, and strategic measures that impact the global economy. The study identifies crucial trends and offers recommendations for sustainable management of contemporary international financial relations.